Congruences on ∼ bisimple right type B ω – semigroups. (4th July 2017) - Li, Chunhua; Xu, Baogen; Huang, Huawei
Abstract: The structure of a ∼ bisimple right typeB ω – semigroup was described by Li, Wang, Xu and Huang as the generalized Bruck-Reilly extensions. As a continuation of their work, in this paper, we shall consider some classes of congruences on such semigroups. It is shown that an arbitrary right * congruence on some classes of ∼ bisimple right typeB ω – semigroups is either an idempotent-separating congruence or a left cancellative congruence.